Organizational modeling in production processes of cluster profiles for urban environments - Lapidus, Azariy Abramovich; Topchiy, Dmitriy Vladimirovich (Revista de la Universidad del Zulia, 2020)
One of the most important aspects of the development of the urban environment is the comprehensive reconstruction of the municipal development territories, with the aim of creating favorable living conditions and the effective use of the production, engineering, scientific, and other potentials of the complex of edification. The structural condition of many industrial buildings means that they can be operated for more than a decade. This coefficient sparks great interest in industrial buildings precisely for the purpose of their redistribution, rather than reconstruction or demolition combined with new construction. The objective of this study is to define an algorithm for organizational and technological construction, in order to determine the redistribution of industrial facilities. The methodology used refers to the dependency graphs of the relative time loss, versus the redistribution coefficient and also the economic efficiency of the project, versus the actual duration of the construction and installation. From this methodology an adequate mathematical model is introduced.